THE INFLUENCE OF SOCIAL COMMUNICATIONS ON THE DEVELOPMENT OF CURRENT TRENDS IN MEDIA EDUCATION - Сикорская, Виктория (SWorldJournal, 2021)
The article examines the features of the influence of social communications on the development of modern trends in media education as a condition for ensuring the development of individual abilities and personal qualities of the learner. The interpretatio